Trial and Error? Reelection Concerns and Policy Experimentation during the US Welfare Reform - Christina Gathmann; Pierre Boyer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We study the political determinants of policy experimentation during the US welfare reform. Among other changes, this reform shifted the autonomy to implement welfare policies from the federal government to the individual states. In line the predictions from a political agency model, we find that (i) governors with high initial reputation among voters experiment less with welfare policies; (ii) governors with lower reelection concerns experiment more; (iii) governors with little experience are more likely to revert an experiment, but are also more likely to stick to a policy experiment with high potential gains. Overall our findings suggest that reelection concerns play an important role for policy experimentation and reversals.
Keywords: I38; H11; D78; 330